Strong mentorships are critical at this juncture in American journalism - Hill, Angela M (Investigative Reporters and Editors, Inc. The IRE Journal, 2017)
Mentorship is a two-way street. It's an opportunity for those who were a part of the first "golden age of journalism" to learn new tricks of the trade from their younger counterparts who are now ushering in a new "golden age of journalism." Hill discusses mentorship benefits for mentees, mentors, and organizations.